INNOVATIVE APPROACH TO THE TREATMENT OF ACUTE PANCREATITIS - D. B. Demin; M. S. Funyguin; A. A. Chegodaeva; Yu. Yu. Solodov (Креативная хирургия и онкология)
In conditions of experimental acute pancreatitis of 60 guinea pigs and during the treatment of 89 patients with acute pancreatitis it was shown that the use of thioctic acid significantly reduces the manifestations of ischemic symptom , the severity of free radical processes and improves the patient's outcomes. The way for minimally invasive interventions under intraoperative ultrasound navigation consists in layered implementation of minimally invasive access of 2-3 cm in length, followed by the establishment of liquid aspiration from the wound channel of necrotic detritus, while emptying and drainaging the cavity under ultrasound control. The method allows one-step sanitation and drainage of cavity formations containing purulent dense necrotic tissue. This method is efficient, technically feasible in any surgical department, economically rational, since it does not require the purchase of additional surgical equipment. This complex of therapeutic measures allowed to reduce postoperative mortality in case of necrotizing pancreatitis to 9 % during the last three years.